Learning to feel well at Jamtli Museum: A case study. Issue 2 (November 2016) - Hansen, Anna
Approximately one-fourth of the population of Sweden will suffer from mental health problems at some point in their lives. This article shares a case study of collaboration between Jamtli Museum and a local hospital (K2) that aimed to provide adult learning opportunities for people with diverse mental health issues. Findings show some differences between how women and men experienced the visits, as well as a marked increase in participants' confidence, social skills and senses of well-being. New knowledge gained on historical agriculture, as well as skills through working experientially with animals, changed how participants viewed their own capabilities and competencies. As a result, cultural heritage organisations such as Jamtli need to be seen as important pedagogical sites that contribute in multiple ways to human well-being.